Data Collection System of IoT Based on the Coordination of Drones and Unmanned Surface Vehicle. (20th February 2023) - Wang, Zhigang; Tian, Liqin; Lin, Lianhai; Xie, Jianfei; Wu, Wenxing; Tong, Yinghua
Abstract : With the continuous renewal and rise of various flight equipment, this article designs a method of water data collection, which is realized through the coordination of an unmanned surface vehicle (USV) carrying unmanned aerial vehicles (UAVs, commonly called drones). In reality, multiple UAVs take-off and landing sites, energy consumption, and other complex issues closely related to USV recovery, UAVs must be considered. If mixed integer linear programming (MILP) is used directly, it is difficult to get satisfactory results in an acceptable time range. Therefore, a heuristic algorithm is proposed to solve the problem of data collection by these devices, which can not only quickly solve the large-scale collaborative optimization problem, but also rationally utilize the total energy consumption of the equipment. The effectiveness of the proposed algorithm is verified and analyzed by experimenting a different number of monitoring nodes, different number of UAVs and different task time. It can not only shorten the cycle of data acquisition task, but also reduce the waiting time of the UAV and USV.